BIỂU HIỆN GEN fliC CẢI BIẾN CỦA Salmonella Dublin VÀ TINH SẠCH FLAGELLIN TÁI TỔ HỢP - Võ, Viết Cường; Trịnh, Văn Toàn; Lê, Thị Lan Anh; Đặng, Thị Việt Hương; Hồ, Thị Hồng Nhung; Nguyễn, Thị Nhung; Đỗ, Thị Huyền; Trịnh, Khắc Sáu (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EXPRESSION OF MODIFIED fliC GENE FROM Salmonella Dublin AND PURIFICATION OF RECOMBINANT FLAGELLIN Flagellin is a potent trigger of innate immune responses that enhance adaptive immune responses. Flagellin has intrinsic adjuvant activity mediated through toll-like receptor (TLR 5) and is an attractive candidate for highly effective vaccine adjuvant. The N-terminal D0-D1 domain of flagellin is required for TLR5 recognition. In the present study, fliC gene from S. Dublin expressed in E. coli BL21 in the fusion form with SUMO protein. The 48 kDa fusion protein of SUMO-flagellin was synthesised in insoluble inclusion body. The overall yield of expressed SUMO - flagellin was 0.6 g/L. The recombinant protein solubilized in 2 M urea then was purified by using Ni-NTA column chromatography with purity about 95.4%. Flagellin will be cleaved from fusion protein and used to develop as a radiation countermeasure.